2010
DOI: 10.4049/jimmunol.1002163
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Hierarchy of Maturity of Murine Memory B Cell Subsets

Abstract: The paucity of murine memory B cell markers has been a significant impediment to the study of memory. The most commonly used marker is IgG, which is neither sensitive nor specific, because activated nonmemory cells can be IgG+, and memory cells can be IgM+. In this article, we show that, together, PD-L2 (CD273), CD80, and CD73 define at least five phenotypic subsets of murine memory B cells. These subsets are generated from naive cells bearing a single BCR in response to a single T-dependent Ag. This diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
226
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(248 citation statements)
references
References 23 publications
(40 reference statements)
11
226
1
Order By: Relevance
“…This process resembles the slower accumulation of plasma cells in the lungs after influenza virus infection (11) and may reflect a requirement for structural alteration and/ or niche formation in the infected lungs for B-cell localization. Although definitive markers of murine memory B cells remain to be identified (12,13), CD73, CD80, and CD273 (PD-L2) are expressed at higher levels on splenic memory than on naïve B cells (14,15). It is also postulated that the proportions of CD80 (6).…”
Section: Resultsmentioning
confidence: 99%
“…This process resembles the slower accumulation of plasma cells in the lungs after influenza virus infection (11) and may reflect a requirement for structural alteration and/ or niche formation in the infected lungs for B-cell localization. Although definitive markers of murine memory B cells remain to be identified (12,13), CD73, CD80, and CD273 (PD-L2) are expressed at higher levels on splenic memory than on naïve B cells (14,15). It is also postulated that the proportions of CD80 (6).…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that MCMV induces poor CD8 T-cell response to challenges with emerging viral infections and that this poor response correlates to the frequency of the (Dogan et al, 2009;Pape et al, 2011;Tomayko et al, 2010). IgM memory B-cells persist long after the clearance of an infection, whereas the conventional memory cells are described as the frontline responders to infections (Good-Jacobson and Tarlinton, 2012).…”
Section: Effects Of Latent Infections On the Peripheral Memory B-cellmentioning
confidence: 99%
“…55 Similar murine "memory" B-cell subsets have also been identified, making it possible to examine the pathogenic role of these BCR-activated B-cell subsets in murine models. 56,57 Recent studies have revealed significant increases in B-cell activation in cGVHD. Compared with B cells in patients without cGVHD, purified peripheral cGVHD B cells were found to be enlarged in size and to contain more total protein per cell, indicating heightened metabolic activity in vivo.…”
Section: Defining Functionally Relevant and Targetable B-cell Subsetsmentioning
confidence: 99%